Magnetic and Electrical Characterization of Nickel-Rich Nife Thin Films Synthesized by Atomic Layer Deposition and Subsequent Thermal Reduction - Escrig-Murua, J; Espejo-Pina, A (Institute of Physics Publishing, 2016)
Nickel-rich NiFe thin films (Ni92Fe8, Ni89Fe11 and Ni83Fe17) were prepared by combining atomic layer deposition (ALD) with a subsequent thermal reduction process. In order to obtain Ni x Fe1-xO y films, one ALD supercycle was performed according to the following sequence: m NiCp2/O3, with m = 1, 2 or 3, followed by one FeCp2/O3 cycle. The supercycle was repeated n times. The thermal reduction process in hydrogen atmosphere was investigated by in situ x-ray diffraction studies as a function of temperature. The metallic nickel iron alloy thin films were investigated and characterized with respect to crystallinity, morphology, resistivity, and magnetism. As proof-of-concept magnetic properties of an array of Ni83Fe17, close to the perfect Permalloy stoichiometry, nanotubes and an isolated tube were investigated. © 2016 IOP Publishing Ltd.